Identifying predictors of treatment response in major depressive disorder: A machine learning approach - Amir, Fattahi; Schrauder, Michael (Revista De Psiquiatria Clinica, 2023)
The essential purpose of research study is determining the predictors related to treatment response in the major depressive d isorder. This research study also represents that machine learning approach between them for analysis. The research based on secondary data analysis for this purpose used different websites related to the variables. the treatment response predictors are main independent variable the depressive disorder is main dependent variable. for measuring the research study used E-views software and generate informative results. The descriptive statistical analysis, the unit root test analysis, the equality test analysis, also that present the co-integration analysis between them. the overall results founded that direct and significant link of predictors of treatment response in the major depressive disorder.
CRIS-Team Scopus Importer:2023-10-06
Keywords: depressive Disorder (DD); E-views software; machine Learning Approach (MLA); Predictors of Treatment response (PTR)